DECOMPRESSIVE CRANIECTOMY FOR ACUTE SUBDURAL HAEMATOMA WITH EXPANSILE DURAPLASTY VERSUS DURAL-SLITS - Khan, Baynazir; Afridi, Ehtisham Ahmed Khan; Khan, Bushra; Khan, Shahbaz Ali; Aurangzeb, Ahsan; Khan, Abdul Aziz; Khan, Wajiha; Bhatti, Sajid Nazir (Journal of Ayub Medical College Abbottabad, 2016)
Background: Traumatic subdural hematoma is one of the lethal injuries to brain. Various surgical techniques are used to evacuate the acute subdural hematoma. The hematoma evacuation can either be done by opening of dura by multiple slits or by opening of dura in single large c shape and then doing the expansile duraplasty. Present study aimed to compare both these techniques. Methods: This randomized control study was conducted in department of neurosurgery, Ayub Medical College, Abbottabad from July 2011 to July 2013. A total of 59 patients were included in this study, which were randomly allocated in two groups (i.e., group A and group B) for decompressive craniectomy. Thirty-one patients were operated by craniectomy with full dural flap opening (Group A), and 28 patients were operated by craniectomy with multidural-slits (Group B). Glasgow Outcome score (GOS) at 6 weeks after the surgery was used to determine the outcome. Results: Mean age of the patients was 33.4±12.8 years. Majority were males. In group A 51.6 % (16) of the patients survived out of which a favourable outcome (GOC 3-5) was observed in 41.9% of the patients, and 9.1% of patients ended up in vegetative state. While in group B 46.4% (13) of the patients survived among which favourable outcome was seen in 39.3% of patients and 7.1% of patients ended up in vegetative state. The difference in outcome measure is insignificant. Conclusion: There was no statistically significant difference among the two groups as regards the mortality, GOS, frequency of complications and hospital. While the duration of surgery was significantly shorter in patients operated with dural slits. Keywords: acute subdural hematoma, decompressive craniectomy, multidural-slits